Literary Review Of Sthoulya(Obesity) And Karshya (emaciation ) In Adolescents Age By Ayurvedic Method - Chauhan, Laxman Naryan; Raut, Deokumar Wamanrao (International Research Journal of Ayurveda & Yoga, 2021)
The important Concept of Ayurveda is keeping of good health. For these all the rules of Rutucharya(seasonal routine), Dinacharya (daily routine) and Ratricharya (our daily routine) should be strictly followed. But in present era of modernization drastic changes in Rutucharya(seasonal routine), Dinacharya (daily routine) and Ratricharya (our daily routine) leads to abnormal dietary habits, modes of life style and various regimens of life style so most of individuals are habituated to luxurious and comfortable lifestyle lead to Sthoulya(Obesity) And Karshya (emaciation ) occurs due to Ruksha Annapana sevan (Indulgence in rough food and drinks), Langhana (Fasting), Pramitashana (Little diet), Kriyatiyoga (Doing more work than Capability), Shoka (Grief), Veganidra Vinighrah, Ruksha Udavartana Snanshyabhyasa (Excess non-unctuous anointing to the person and after that indulgence in bath), Prakruti (Constitution) leads to Karshya(emaciation).The causative factor, Etiopathogenesis, Symptoms and Managements of Sthoulya(Obesity) And Karshya (emaciation ) will be discussed below.